Desain Didaktis Berpendekatan TaRL Berbantuan Media Flashcard untuk Menjembatani Kemampuan Perkalian Konkret dan Simbolik Siswa Kelas 3 di SDN 2 Labuapi - Asri Nadiatullah; Mohammad Archi Maulyda; Ni Made Yeni Suranti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to describe how a didactical design based on the Teaching at the Right Level (TaRL) approach, supported by flashcard media, can bridge third-grade students’ concrete and symbolic multiplication abilities at SDN 2 Labuapi. This research employed a qualitative method using a didactical scenario research design. The subjects of this study consisted of one third-grade teacher and 24 third-grade students at SDN 2 Labuapi. Data were collected through observation, interviews, and tests. The findings showed that in the first meeting, all levels achieved an average score of 100. In the second meeting, differences in average scores began to emerge across each level. The average score of the low level was 80, the medium level was 92.5, and the high level was 97.5. In the third meeting, students’ average scores showed further improvement. The average score of the low level increased to 95, while both the medium and high levels once again achieved a score of 100. In the fourth meeting, the average scores of the medium and high levels remained at 100, while the low level showed another improvement, reaching approximately 97.5. This study contributes significantly as a source of ideas and scientific literature for other researchers regarding the TaRL approach, conceptual representation, students’ cognitive processes, and the role of learning media.